'I can't understand why others don't screen more': a qualitative study exploring why Australian general practitioners screen for primary aldosteronism. Issue 6 (13th June 2022) - Nainani, Abhir Krishan; Yang, Jun; Peters, Sanne; Russell, Grant
Abstract : Objective: We sought to understand the factors that influence a general practitioner's (GP's) experience of screening for primary aldosteronism (PA) in hypertensive patients. Design: A qualitative study, framed by phenomenology, using semistructured interviews that were audiorecorded, transcribed verbatim, entered into NVivo V.12.0 for coding and analysed for emerging themes. Setting: Melbourne, Australia. Participants: Eligible GPs had received education on PA as part of a previous study. We recruited a purposive sample of 16 GPs (6 females, 10 males) who varied in practice location, clinical experience and the number of patients screened for PA. Results: Although GPs had been educated about PA, they found it challenging to explain the condition to patients and were uncertain about how to screen patients who were already taking antihypertensive medications. Most viewed the screening process to be practical, inexpensive and, by and large, acceptable to their patients. However, they found it inconvenient to alter antihypertensive medications before screening to allow for easier interpretation of the aldosterone-renin ratio. They were also less enthused about screening patients whom they thought fitted a clinical picture of essential hypertension. Knowledge of the screening process, cost and convenience of performing the aldosterone–renin ratio, conceptualisation of risk related to PA, and a desire to improve clinical care were influencing factors that modified the GPs' screening experience. Conclusion: Our findings suggest that knowledge gaps, practical limitations of the aldosterone–renin ratio, and errors in diagnostic reasoning were challenges of routine PA screening. Most of these practical barriers could be addressed by relatively simple educational and practice modifications to increase PA screening rates and optimise detection for the most common cause of secondary hypertension in primary care.